Psychomotor profile of scholarly children (6 and 10 years old) in Pereira city, Colombia - Pedro Antonio Calero Saa (Revista de Educação Física, 2016)
Introduction: The psychomotor profile of children is directed related to the psychomotor development, understood as a process of continuous evolution that happens over the years. Objective: This article attempts to determine the psychomotor profile of children aged between 6 and 10 years, from educational institutions in the city of Pereira, Risaralda (Colombia). Methods: Through a cross descriptive quantitative study with a comparative phase, 26,448 children were eligible to participate the study, meeting the inclusion criteria. From them, a sample of 420 children aged between 6 and 10 years was selected, obtained from the formula for finite populations, with a prevalence of 44% of reference; sampling was a simple random. The instrument used was the Vitor da Fonseca’s test battery of psychomotor development. Chi-square was used to evaluate association of age, education level and residential community with level of confidence of 95%. Results: The sample was composed of 222 girls (52.9%; CI 47-56) and 198 boys (47%; CI 42-51). 90.2% (95%CI 87-92) presented psychomotor profile classified as Good (Eupraxic) while 4.0% (95%CI 3-4) were on Satisfactory (Dyspraxic) range and 5.7% (95%CI 4-5) exhibited Excellent (Hyperpraxic) psychomotor profile. Conclusion: In general, the children evaluated presented adequate psychomotor development. Results according to the factors (Tonicity, Laterality, Body Notion, Balance, Time Space, Global Praxia and Fine Praxia) were discussed.